Effects of public perception on urban planning: evolution of an inclusive planning system during crises in Latvia. Issue 1 (January 2016) - Liepa-Zemeša, Māra; Hess, Daniel Baldwin
Abstract : This article explores changes in public perception of urban planning practice in Latvia during a period of economic crisis. Detailed analyses of the development of the planning systems in Latvia after the disintegration of the Soviet Union and restoration of independence (in 1991) are used to trace changes in public perception of urban planning over two decades during both economic upturns and downturns, beginning with the transition period from centralised planning during the totalitarian era to an inclusive planning system in a democratic society. Economic data describing the crisis and survey data gauging public reaction to them are used to synthesise evidence about public participation in urban planning exercises. Findings suggest that external factors strongly impact community perceptions of planning and that the public is willing to engage after first achieving individual goals. Events in Latvia in recent years suggest that crises serve as triggers for community engagement in planning and turning points in public perception of urban planning.